Effect of vitamin B12 supplementation on glycemic control in poorly controlled hyperhomocysteinemic type 2 diabetic patients (Bangladesh Journal of Pharmacology, 2015)
This study was conducted to observe the effect of vitamin B12 supplementation on glycemic control in poorly controlled hyperhomocysteinemic type 2 diabetic patients by measuring HbA1c levels at baseline and 4 weeks. Patient having serum homocysteine more than 15 µmol/L or vitamin B12 less than 223 pg/mL were enrolled in this study. One group received methylcobalamin 500 µg daily with their usual anti-diabetic therapy and the other group received only suitable anti-diabetic drug therapy. Methylcobalamin 500 µg was given daily for period of 4 weeks. Glycemic control was measured by levels of HbA1c, blood sugar at baseline and at 4 weeks. Serum homocysteine levels was reduced from 21.5 ± 2.6 to 15.4 ± 6.4 (p=0.04) with vitamin B12 supplementation at 4 weeks. At 4 weeks, HbA1c decreased from 9.9 ± 0.9 to 8.7 ± 0.5 (p